2000
DOI: 10.1142/s0218863500000212
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Response of Cyanobiphenyl Liquid Crystals to High-Power, Nanosecond Laser Radiation

Abstract: Results from investigations are summarized into: (1) transient refractive and absorptive (two-photon) nonlinearities at 0.532 μm by the Z-scan method, and (2) reflective nonlinearity in the near-IR, of linearly nonabsorbing cyanobiphenyl liquid crystals under nanosecond laser irradiation. (1) For isotropic liquid crystals at the several-nanosecond time scale and several tens-micrometers beam-waist-diameter, transient molecular-reorientation and thermal/density refractive nonlinearities compete in changing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 121 publications
0
26
0
Order By: Relevance
“…The only shortcoming, a value of n 2 independent on T on approaching the transition temperature T c to the isotropic phase, could be explained by a slowing down of the orientational relaxation for T → T c [17]. At these short time scales, many puzzles remain, like the unexpected large value of β at nanosecond time scale, 10-to 10 2 times larger than that in the picosecond time scale [16]. To account for this result, it was suggested the possibility of formation of µm-sized bubbles and microscopic carbonization in the sample during the laser exposure.…”
Section: Electronic Nonlinear Optical Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The only shortcoming, a value of n 2 independent on T on approaching the transition temperature T c to the isotropic phase, could be explained by a slowing down of the orientational relaxation for T → T c [17]. At these short time scales, many puzzles remain, like the unexpected large value of β at nanosecond time scale, 10-to 10 2 times larger than that in the picosecond time scale [16]. To account for this result, it was suggested the possibility of formation of µm-sized bubbles and microscopic carbonization in the sample during the laser exposure.…”
Section: Electronic Nonlinear Optical Processmentioning
confidence: 99%
“…Other important features that influence the magnitude and sign of the nonlinear refraction index are the beam waist and the thickness of the sample (ref. [16] and references therein). In the case of the isotropic phase of the 5CB it was observed that increasing the beam waist from 7 µm to 35 − 50 µm, n 2 changes from negative to positive.…”
Section: Electronic Nonlinear Optical Processmentioning
confidence: 99%
“…Sharp texture transformations of SmA-SmC * , SmC * -Cr2, and Cr2-Cr1 give abrupt changes in the values of AC. The optical transmittance of the sample is inversely proportional to AC [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…These experiments have shown the stability of CLCs with mixtures of cholesterol esters in the field of high-powered nanosecond single pulsed lasers. Other authors have observed the untwisting of a cholesteric helix in the field of light waves [73][74][75][76][77][78][79], which is manifested by a reduction of the selective reflection under irradiation by laser pulses with a duration of §500 ns, at a repetition rate of 4.5 kHz, and at a power density of more than 1 MW/cm 2 [73].…”
Section: Cholesteric Liquid Crystalmentioning
confidence: 99%